Divine Words, Cramped Actions: Walter Benjamin ― an Unlikely Icon in Translation Studies - Sanders, Janet (TTR)

(untitled) (Association canadienne de traductologie, 2003)
AbstractFor the last half century Walter Benjamin has had almost legendary status in the world of translation studies. Scholars have been fascinated by the ideas in The Task of the Translator, but almost none has looked at how—or even whether—Benjamin actualized his philosophy, either in his own practice of translation or in his criticism of translations by others. This is the purpose of the present article.